An Investigation of the Alleged Discriminatory Impact of General Credit Controls in Periods of Monetary Stringency - Haymes, Harmon Hayden (Journal of Finance, 1959)
Harmon Hayden Haymes, An Investigation of the Alleged Discriminatory Impact of General Credit Controls in Periods of Monetary Stringency, The Journal of Finance, Vol. 14, No. 4 (Dec., 1959), pp. 565-566